2007
DOI: 10.1002/ppap.200731501
|View full text |Cite
|
Sign up to set email alerts
|

Production and Control of Large-Area Plasmas for Meters-Scale Flat-Panel-Display Processing with Multiple Low-Inductance Antenna Modules

Abstract: Plasma technologies for meters‐scale flat‐panel‐display (FPD) processing have been developed using multiple low‐inductance antenna (LIA) modules to drive inductively coupled plasmas (ICPs), in which RF‐power‐deposition profiles can be controlled in plasma reactors with a scale as large as meters. The LIA module consisted of a U‐shaped internal antenna with dielectric isolation, each of which was coupled to an RF power system for independent power control of driving ICP. Our new proposal of the unique source co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
2
2

Relationship

4
4

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 19 publications
1
35
0
Order By: Relevance
“…This tendency for having a peak at the center of the substrate and/or the center of the deposition chamber is due to the nature of significant charged-particle loss at the side walls, which in turn makes the plasma profile tend to peak at the center. Furthermore, this tendency of the non-uniform profile is confirmed to be consistent with our previous results for the film thickness distribution of the hydrogenated amorphous carbon films [21].…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…This tendency for having a peak at the center of the substrate and/or the center of the deposition chamber is due to the nature of significant charged-particle loss at the side walls, which in turn makes the plasma profile tend to peak at the center. Furthermore, this tendency of the non-uniform profile is confirmed to be consistent with our previous results for the film thickness distribution of the hydrogenated amorphous carbon films [21].…”
Section: Resultssupporting
confidence: 89%
“…In order to provide straightforward and promising solutions to overcome the problems described above, a series of our works [17][18][19][20][21] have been carried out on the basis of the plasma-generation and profile-control technologies employing multiple low-inductance antenna (LIA) modules, whose antenna size is substantially shorter than the propagation wavelength, to sustain meter-scale inductivelycoupled plasmas, whose concepts are schematically shown in Fig. 1.…”
Section: Basic Concepts Of Plasma-generation and Profile-control Techmentioning
confidence: 99%
“…In our previous studies [10][11][12][13][14][15][16], we have demonstrated that this unique antenna for ICP generation allows high-density (10 11 -10 12 cm − 3 ) plasma production with low plasma damage (as low as 10 V) via low-voltage operation of ICPs. Furthermore the internal-antenna configuration with the LIA units has the feature of flexibility to meet various configurations of plasma sources.…”
Section: Introductionmentioning
confidence: 97%
“…In our previous studies [10][11][12][13][14][15][16], we demonstrated that the configuration with multiple LIA units for ICP generation allowed high-density (10 11 -10 12 cm − 3 ) plasma production with high power-transfer efficiency (as high as 90%) and low plasma potential (as low as 6 V). The ICP sources with LIA units are considered to be one of the most promising candidates as plasma sources for low-damage and high-quality processes [17,18].…”
Section: Introductionmentioning
confidence: 98%